2017
DOI: 10.1186/s12936-017-1946-1
|View full text |Cite
|
Sign up to set email alerts
|

Progress in coverage of bed net ownership and use in Burkina Faso 2003–2014: evidence from population-based surveys

Abstract: BackgroundUse of insecticide-treated bed nets (ITNs) is the cornerstone of malaria prevention. In 2010 and 2013, the Burkina Faso Government launched mass distribution campaigns of ITNs to increase coverage of ownership and use in the country. This study assessed the progress towards universal bed net coverage in Burkina Faso.MethodsThe authors used data from the Burkina Faso 2003 and 2010 Demographic and Health Surveys (DHS), the 2006 Multiple Indicator Cluster Surveys (MICS) and the 2014 Malaria Indicator Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
5
15
0
Order By: Relevance
“…Large household size (≥7 family members) as the main associated factor for households with insufficient access to LLINs (less than one LLINs for every two persons) is not surprising, and is in line with recent findings in Sierra Leone [ 38 ] and Burkina Faso [ 39 ] where available ITNs at household were not able to protect all family members. Besides household size, socio-demographic characteristics of household heads and cooking practices using firewood were also independently associated with limited LLIN access.…”
Section: Discussionsupporting
confidence: 85%
“…Large household size (≥7 family members) as the main associated factor for households with insufficient access to LLINs (less than one LLINs for every two persons) is not surprising, and is in line with recent findings in Sierra Leone [ 38 ] and Burkina Faso [ 39 ] where available ITNs at household were not able to protect all family members. Besides household size, socio-demographic characteristics of household heads and cooking practices using firewood were also independently associated with limited LLIN access.…”
Section: Discussionsupporting
confidence: 85%
“…Future analysis will examine ITN access as it relates to ITN use in Burkina Faso.When examining ITN usage by community level, ITN use was signi cantly associated with malaria prevalence, residence, and region. While these factors are interrelated, it does highlight that there are places within Burkina Faso that should be prioritized for future social behavior messaging focused on increasing ITN usage.Previous studies have shown that over time, the Centre Region has consistently displayed high ITN usage, most likely re ective of the population in the Centre Region, which is concentrated in urban areas (Ouagadougou)[26]. This analysis aligns with prior research that found rural areas to have lower odds of ITN use as compared to urban areas, and all other regions in the country having lower odds of ITN usage as compared to the Centre Region.…”
supporting
confidence: 85%
“…Even though clinical and statistical significance was found for ITNs, in reality the effectiveness of interventions (ITN) are dependent on a number of extrinsic factors such as population behaviour and vector aetiology. Studies have shown that ITN use is influenced by social behaviour including education, level of knowledge on malaria, and ease of use [ 106 , 107 ]. In addition, other socio-economic factors such as working and staying overnight in the forest decreases protection despite high proportion of coverage by ITNs [ 108 – 110 ].…”
Section: Discussionmentioning
confidence: 99%